Case report – Kidney-Lung Syndrome (Goodpasture Syndrome) when to think - Ribeiro, Thais Maryana; Merlos, Fernando; Filho, Sergio Luis Spitzner; Fernandes, Pedro Henrique Dias; Carraro, Priscila Gabriella (Seven Editora, 2024)
Lung-kidney syndrome is an anti-glomerular basement membrane (anti-GBM) disease, which is often characterized by pulmonary hemorrhage and renal dysfunction. To date, no specific trigger for the development of anti-GBM antibodies has been identified, and exposure of the alveolar capillaries to these antibodies requires an initial attack on the pulmonary vasculature, resulting in a typical picture of glomerulonephritis. As it is a disease of low prevalence, clinical reasoning associated with an effective investigation for early detection is essential for a satisfactory evolution. Good results are seen when treatment is started immediately. Thus, the present case report aims to discuss, through a literature review in databases such as Scielo and PubMed, the efficacy of an early intervention in a patient with initially unexplained respiratory failure and renal dysfunction, associated with alterations in laboratory and imaging tests. In addition, it aims to demonstrate the importance of quick clinical reasoning to avoid sequelae and increase the chances of a good prognosis. DOI:https://doi.org/10.56238/sevened2024.026-062